2019
DOI: 10.1111/jpm.12573
|View full text |Cite
|
Sign up to set email alerts
|

Treating mental health crises at home: Patient satisfaction with home nursing care

Abstract: Accessible SummaryWhat is known on the subject? Most studies have focused on whether hospital admissions have been reduced by the introduction of crisis services, rather than focusing on how these services are employed. Research has also shown that home assistance decreases costs and increases the level of patient satisfaction, thereby being more efficient in terms of the cost/effectiveness ratio than is traditional hospital care. Patient satisfaction with nursing care has long been identified as a key elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…We contacted the corresponding authors of nine studies to request additional information on: 1. the clinical setting where fieldwork was conducted [ 29 , 30 , 31 ], 2. the population and sample size [ 30 , 31 , 34 , 37 , 41 , 55 ], 3. ethics approval [ 64 ] and 4. approach to data analysis [ 28 , 40 ]. As of the 27 June 2022, two authors, [ 28 , 37 ] responded, providing the requested information that we incorporated in the risk assessment data extraction tables, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We contacted the corresponding authors of nine studies to request additional information on: 1. the clinical setting where fieldwork was conducted [ 29 , 30 , 31 ], 2. the population and sample size [ 30 , 31 , 34 , 37 , 41 , 55 ], 3. ethics approval [ 64 ] and 4. approach to data analysis [ 28 , 40 ]. As of the 27 June 2022, two authors, [ 28 , 37 ] responded, providing the requested information that we incorporated in the risk assessment data extraction tables, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, nursing satisfaction related to caregiving has been primarily associated with inferring satisfactory signs from clients(Yamamoto-Mitani et al, 2018). As also indicated in the study ofGiménez-Díez et al, 2019) the health agent plays an important role in the patient's recovery in CRHTTs and care becomes personalized, which is why the therapeutic relationship becomes significant and satisfactory for the persons implicated. This satisfaction was also found in our findings Harris and Panozzo, (2019).…”
mentioning
confidence: 89%
“…The service is designed to reduce hospital admissions and help patients return home promptly after an acute admission to a psychiatric hospital (Lloyd-Evans et al, 2018). This modality has been considered less invasive and traumatic than hospital admissions (Giménez-Díez et al, 2019). It allows greater participation, improved quality of life and increased privacy for patients (Barker & Buchanan-Barker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, previous studies on satisfaction with the services provided by LTCFs have reported that residential environment, costs paid by users, services, and the professionalism of the staff are key factors affecting satisfaction [15][16][17][18]. In addition, a smaller size, nonprofit ownership, rural location, lower cost, and higher staff expertise were associated with greater family satisfaction [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, previous studies on satisfaction with the services provided by LTCFs have reported that residential environment, costs paid by users, services, and the professionalism of the staff are key factors affecting satisfaction [15][16][17][18]. In addition, a smaller size, nonprofit ownership, rural location, lower cost, and higher staff expertise were associated with greater family satisfaction [15][16][17][18]. In Korea, satisfaction with general lifestyle management services (such as eating, housework, and bathing) provided to older adults residents is high, whereas satisfaction with services that require professionalism (such as social participation and medical services) is poor [19].…”
Section: Introductionmentioning
confidence: 99%